2015
DOI: 10.2527/jas.2014-8380
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary electrolyte balance on feed preference and growth performance of postweaned piglets1

Abstract: A total of 672 male and female piglets (21 d postweaning; approximately 13 kg BW) were selected to be used in 3 different experiments to assess the influence of dietary electrolyte balance (dEB; Na + K - Cl, in mEq/kg of diet) on feed preference and growth performance. In Exp. 1, piglets were fed 4 isoenergetic diets differing in dEB level: 16, 133, 152, and 269 mEq/kg diets. Changes on dEB were obtained by changing the levels of sodium and chloride with calcium chloride, calcium carbonate, and sodium bicarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
1
20
1
1
Order By: Relevance
“…Because many common U.S. nursery diet formulations exceed 150 mEq/kg, these results are important. However, the results from Guzman-Pino et al (2015) contradict those who reported improved growth performance with increasing dietary dEB ( Patience et al, 1987 ; Dersjant-Li et al, 2001 ; DeRouchey et al, 2003 ). To solve the discrepancies among literatures, this study aimed to evaluate the impact of dEB on growth performance of nursery pigs in a commercial scale research facility.…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Because many common U.S. nursery diet formulations exceed 150 mEq/kg, these results are important. However, the results from Guzman-Pino et al (2015) contradict those who reported improved growth performance with increasing dietary dEB ( Patience et al, 1987 ; Dersjant-Li et al, 2001 ; DeRouchey et al, 2003 ). To solve the discrepancies among literatures, this study aimed to evaluate the impact of dEB on growth performance of nursery pigs in a commercial scale research facility.…”
Section: Introductioncontrasting
confidence: 65%
“…Traditionally, the optimal dEB for pigs is reported to be approximately 250 mEq/kg ( NRC, 2012 ), but limited research exists in this area. Recently, Guzmán-Pino et al (2015) used CaCl 2 to reduce dEB and reported that nursery pigs had reduced ADG and G:F when dEB exceeded 150 mEq/kg; in addition, ADG was improved by 48.7% by decreasing dEB from 269 to 16 mEq/kg. Because many common U.S. nursery diet formulations exceed 150 mEq/kg, these results are important.…”
Section: Introductionmentioning
confidence: 99%
“…Animal feed adds minerals not only to satisfy the mineral requirements but also to modify the dietary electrolyte balance (EB) [129]. e balance between cation (Na+) and anions (K + /Cl -) and the acid or alkaline load from the diet may strongly alter the acid-base status and growth performance of weaned piglets [130,131]. It is reported that an excess of chloride ions induces a negative dietary EB and reduces the growth performance of weaned piglets [132][133][134].…”
Section: E Effect Of Dietary Electrolyte Balance On the Growth Performentioning
confidence: 99%
“…In short, a dietary addition of minerals in postweaning diets, such as calcium chloride and sodium bicarbonate, could affect the EB and significantly alter the feeding behavior, apparent digestibility, and productive performance of postweaned piglets. Additionally, piglets showed a bias toward low-EB diets, which optimized their performance more so than that for high-EB diets [130,135].…”
Section: E Effect Of Dietary Electrolyte Balance On the Growth Performentioning
confidence: 99%
See 1 more Smart Citation